(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Twelve of reinforced concrete beams, with (hollow and Solid) square section tested under pure torsion, with dimensions of 160 mm height and 1000 mm length. The effects of steel fiber percentage and concrete core on ultimate torsional were studied, as well as the crack torsional capacity and angle of twist. For solid section an increase of 98.2% and 178%, and for hollow section an increase of 91.3% and 163%in the ultimate and crack torsional capacity respectively obtained when steel fibers percentage was increasing from zero to 2.5%.Transverse and longitudinal reinforcement ratios were kept constant. Experimental study showed that, the ultimate torsional strength and beam elongation were not affected by concrete core.